Impact of Dielectric Constant on Embedded Antenna Efficiency - Van Thuan Nguyen; Chang Won Jung (International Journal of Antennas and Propagation)
The impact of dielectric constant on radiation efficiency of embedded antenna located inside human body or another liquid environment is investigated both analytically and numerically. Our research is analysed and simulated at 403 MHz in the MedRadio band (401–406 MHz) and within a block of 2/3 human muscle phantom. Good agreement is achieved between analysis and simulation results. This work provides a guidance in selecting insulator for embedded antennas.